Danijos moterų ir lyties informacjios bei dokumentacijos centras - KVINFO - Stundžienė, Lijana (Information & Media, 1995)
The survey examine The Danish Centre for Information on Women and Gender (KVINFO). KVINFO gives information on women's and gender studies, researchers and research centres in Denmark. Also KVINFO is a research library open to the public. The library lends books, periodicals, theses and another unpublished materials. KVINFO houses Danish Women's Photo archive, major Nordic and Danish research projects.The Center was founded in 1979 by N. Koch. KVINFO was inadequately and irregularly financed until an action plan for women's studies in Denmark was initiated in 1986. Nowadays KVINFO has governing body of 9 persons representing different institutions and women's organizations. Since 1990 E. Moller Jensen has been the director of KVINFO.Collections: 9000 books, 340 current periodicals and magazines etc. 40% of the collections is in Danish, 60% in foreign languages, mainly English.Until 1987 all material was filed in a card catalogue. Then KVINFO became part of the Danish libraries' joint data base, DANBIB. Today the catalogue is also part of the Royal Library's data base, REX. KVINFO has direct access to Danish and international bases and several CD ROM's.KVINFO publishes "FORUM, tidsskrift for kon og kultur" (Magazine of Gender and Culture), founded in 1981 and until 1992 the only Danish Women's studies journal. FORUM is published 4 times a year.Vilnius University Women's Studies Center is in touch with KVINFO and gets list of new titles on women from KVINFO.